Development of Tenderized Fermented Squid Product in the Form of Spread and Pieces Using Kiwifruit Protease - Chacko, Priyanka (Auckland University of Technology, 2016)
Squids are cephalopods widely used as food in many cultures, where they are customarily cooked as a means of enhancing nutritional value, and as a way of temporarily preserving squid from spoilage. Modelled on a cooked, comminuted and fermented mussel product developed at AUT, this project primarily aimed to develop a tenderized fermented squid product in the form of spread or pieces. Squid mantle is chewy by virtue of its high collagen content. While this may appeal to some consumers, the New Zealand culinary tradition uses kiwifruit proteases to minimise this chewiness. Zyactinase, a standardized kiwifruit protease was used in this study as well as freshly prepared kiwifruit extract. Various product forms such as minced, bowl chopped and chopstick-suitable pieces were compared. Irrespective of the use of enzyme, during the preparation of fermented product, minced and bowl chopped squid mantles expanded when the required evacuation was applied. This was undesirable. It was laborious to expel all the gas from the system necessary for the subsequent anaerobic fermentation. It was also noticed that the finer the cut the harder it was to achieve the required vacuum. Light and electron microscopy revealed the fine structure of squid mantle, which led to this packaging problem. Therefore the preparation of finely comminuted squid spread was discontinued. Chopstick-suitable fermented pieces were more promising because they could be easily vacuum packed. The cooking step prior to evacuation and fermentation was thought to be a useful way of limiting the protease activity through enzyme denaturation. Over tenderized squid develops a mushy texture, and exposure to protease also led to a yellowing of squid mantle, possibly linked to the Maillard reaction. Thus the tenderizing effects of the kiwifruit protease preparations were examined under varying conditions of concentration, pH and incubation period. Based on the earlier experiments with comminuted squid, 1% Zyactinase to the weight of the squid tissue was chosen as the starting point for tenderising the chopstick-suitable fermented product. However, it took overnight incubation to tenderise the mantle pieces. In contrast, freshly prepared kiwifruit was highly effective in tendering squid pieces when marinated for only five hours. Thus, the tendering ability of Zyactinase was questionable. The pH of the incubation medium can influence the texture of squid mantle, and it was found that acidic conditions toughened the mantle pieces irrespective of the presence of protease. This could be linked to the denaturation effect of food acids in the same way that the raw fish becomes sushi on the addition of lemon juice or vinegar. Fermentation was successful throughout the studies, with or without enzymes. The lactic acid produced might be anticipated to affect texture, but there were no significant difference in the textural values of squid pieces between after enzyme incubation and after fermentation, when enzyme incubations were conducted at ambient pH. In respect of tenderising, the springiness of the squid pieces was close to unity in most of the preparations with or without enzyme under varying pH and incubation times. However, a slight but significant drop in toughness was found for pieces after fermentation In conclusion, cooked fermented squid pieces could be commercially produced in a commercial environment, but Zyactinase is not effective as a tenderiser.
Keywords: Squid; Fermented Product; Kiwifruit Protease; Squid Tenderization